Long-term antithrombotic therapy after venous stent placement. (July 2020) - Lin, Chenyu; Martin, Karlyn A; Wang, Mei; Stein, Brady L; Desai, Kush R
Objectives: To examine the prescribing patterns and outcomes of antithrombotic regimens after venous stent placement. Methods: A total of 87 patients who received inferior vena cava or iliofemoral venous stents were included in the study. A retrospective review was performed to determine the antithrombotic regimens and the subsequent rates of in-stent restenosis, stent thrombosis, and bleeding. Results: The prescribing patterns of specific antithrombotic regimens were highly variable. In-stent restenosis and stent thrombosis events were observed in 13 of 63 patients (21%) with available follow-up imaging, while major bleeding events were noted in 6 of 87 patients (7%). Triple therapy appeared to reduce the odds of in-stent restenosis/ stent thrombosis when compared to dual antiplatelet therapy (OR = 0.07, P  = 0.01). Conclusions: Substantial variability exists in antithrombotic therapy following venous stenting at our institution. This study demonstrated a reduction of in-stent restenosis/thrombosis events when utilizing triple therapy compared to antiplatelet-only regimens. However, larger prospective trials are needed to more accurately determine the relative risks and benefits of each antithrombotic regimen.